Проблема сексизму в it: індивідуальні можливості протидії тендерної дискримінації - Носач, А. А. (ХНУРЕ, 2019)
In the Ukrainian IT sector, the proportion of women workers is steadily increasing. Therefore, the issue of combating gender discrimination in this area is becoming very relevant. People often come up with their estimates of stereotyped ideas about the role and characteristics of men and women. These stereotypes extend to both the domestic and professional sphere, preventing both women and men. It is important to realize which of the daily activities are sexist or can be understood by people in this way. It is worth treating everyone impartially and assessing professional skills and personal qualities rather than classifying people based on their gender, faith, nationality and appearance